Mid-Infrared Photonic Sensors: Exploring Fundamentals, Advanced Materials, and Cutting-Edge Applications - Muhammad A. Butt; Marcin Juchniewicz; Mateusz Słowikowski; Łukasz Kozłowski; Ryszard Piramidowicz (Sensors)
Mid-infrared (MIR) photonic sensors are revolutionizing optical sensing by enabling precise chemical and biological detection through the interrogation of molecules’ unique vibrational modes. This review explores the core principles of MIR photonics, emphasizing the light–matter interactions within the 2–20 µm wavelength range. Additionally, it examines innovative sensor architectures, such as integrated photonic platforms and optical fibers, that enhance sensitivity, specificity, and device miniaturization. The discussion extends to groundbreaking applications in environmental monitoring, medical diagnostics, industrial processes, and security, highlighting the transformative impact of these technologies. This comprehensive overview aims to illuminate the current state-of-the-art while inspiring future developments in MIR photonic sensing.